2022-LBA-1703-ESGO Survival outcomes in minimally invasive surgery versus abdominal surgery for cervical cancer-retrospective cohort from a high-volume Canadian center (2006–2017). (27th October 2022) - Samouëlian, Vanessa; Feng-Emond, Audrey; Cormier, Béatrice; Warkus, Thomas; Bacha, Omar Moreira; Hillmann, Elise de Castro
Abstract : Introduction: MIS has been abandoned in many centers for cervical cancer treatment after publication of the LACC trial in 2018. Several critics and theories emerged afterward. Our study looked at data of a single large volume institution. Disease free survival (DFS) and mortality rates were compared for both surgical approaches. Methods: We retrospectively reviewed all surgical cervical cancer cases from 2006 to 2017 of the Centre Hospitalier de l'Université de Montréal. Only patients treated by Minimal Invasive Surgery (MIS) or laparotomy were included. We compared cohorts' characteristics and survival outcomes for MIS and laparotomy. Descriptive data is presented in means, standard deviations, and percentages. Kaplan-Meier was used to generate disease free survival (DFS) and overall survival (OS) curves; log-rank was used to compare curves. Survival outcomes of the use of intrauterine manipulator were also investigated. Statistical significance was 0.05. Results: 257 patients were included (94 robotic, 38 laparoscopy, 125 laparatomy). Patients' characteristics did not significantly differ among groups. Histology was 50.6% squamous cell carcinoma, 35.4% adenocarcinoma, 3.9% adenosquamous and 10.1% other subtypes. Patients were FIGO stages IA (51.0%), IB (43.1%) and IIA or more (5.9%). Median follow-up was 161 months. Intrauterine devices were used in 70.2% of the MIS group. 48.8% had no residual disease at surgery. No differences in intra-operative, post-operative complications and readmission rates between MIS and laparotomy was observed. Total cohort intra-operative and post-operative complications rates were respectively 4.5% and 25, 2%. Recurrence rates and death rates were significantly lower for MIS than for laparotomy approach (respectively 1.5% vs 8.1%, p=0.013, 1, 5% vs 4, 8%, p=0.043). Disease-specific mortality rate did not statistically differ (MIS=1.5%, laparotomy =4.8%, p=0.121). Conclusions: Selected cervix cancer patients may benefit from MIS. Further studies are needed.